2008
DOI: 10.1021/jm7011276
|View full text |Cite
|
Sign up to set email alerts
|

Development of Prodrug 4-Chloro-3-(5-methyl-3-{[4-(2-pyrrolidin-1-ylethoxy)phenyl]amino}-1,2,4-benzotriazin-7-yl)phenyl Benzoate (TG100801): A Topically Administered Therapeutic Candidate in Clinical Trials for the Treatment of Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is one of the leading causes of loss of vision in the industrialized world. Attenuating the VEGF signal in the eye to treat AMD has been validated clinically. A large body of evidence suggests that inhibitors targeting the VEGFr pathway may be effective for the treatment of AMD. Recent studies using Src/YES knockout mice suggest that along with VEGF, Src and YES play a crucial role in vascular leak and might be useful in treating edema associated with AMD. Therefore, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Palanki and co-workers (TargeGen) identified prodrug candidate 333 , an inhibitor of Src kinase and VEGFr ( Scheme 72 b). 243 This compound was active against age-related macular degeneration, a main cause of vision loss. To obtain intermediate 332 , 4-(2-pyrrolidin-1-ylethoxy)bromobenzene was combined with 3-amino-1,2,4-triazine in moderate yield.…”
Section: Heteroanilinesmentioning
confidence: 99%
“…Palanki and co-workers (TargeGen) identified prodrug candidate 333 , an inhibitor of Src kinase and VEGFr ( Scheme 72 b). 243 This compound was active against age-related macular degeneration, a main cause of vision loss. To obtain intermediate 332 , 4-(2-pyrrolidin-1-ylethoxy)bromobenzene was combined with 3-amino-1,2,4-triazine in moderate yield.…”
Section: Heteroanilinesmentioning
confidence: 99%
“…Currently, it is in clinical trials for the treatment of AMD and has potential application for corneal neovascularization. 37 …”
Section: Translational Implicationsmentioning
confidence: 99%
“…The results indicated that all the six VEGFR-2 active phthalazine derivatives (47-52, IC 50 = 48-120 nM) also displayed good activity against VEGFR-1 with the IC 50 330 nM range. Another two compounds (53, 54) showed good potential for the development as VEGFR-2 specific inhibitors (15-20 fold) against VEGFR-1.…”
Section: Antiangiogenic Agents Of Phthalazine Typementioning
confidence: 99%
“…The in vivo anticancer activity of (79) was identified in a L2987 human lung carcinoma xenografts in athymic mice. A series of substituted benzotriazines was disclosed as potent inhibitors of VEGFR by Palanki in 2008 [50]. One of the most potent compounds was (80), a dual inhibitor of both VEGFR-2 and Src family kinases.…”
Section: Antiangiogenic Agents Of Triazine Typementioning
confidence: 99%